A Green, Solvent‐Free, Microwave‐Assisted, High‐Yielding YbCl3 Catalyzed Deprotection of THP/MOM/Ac/Ts Ethers of Chalcone Epoxide and 2′‐Aminochalcone and Their Sequel Cyclization. (26th October 2015) - Kumar, Sumit; Verma, Nishant; Parveen, Iram; Ahmed, Naseem
Abstract : Abstract : Under microwave and solvent‐free conditions, YbCl3 efficiently catalyzed thedeprotection of tetrahydropyran‐2‐yl, methoxymethyl (MOM), acetyl, and tosyl groups and sequelcyclization of chalcone epoxide to 2‐hydroxyindanone and 2′‐aminochalcone to aza‐flavanone. The reaction afforded the products in excellent yield (78–99%) at 850 W microwave heating within 1–5 min under eco‐friendly conditions. The merits of the presented protocol include high yield, use ofmicrowave irradiation, solvent‐free condition, catalyst reusability, and no need for purification with column chromatography. The present method is very much milder but more advanced than those reported earlier.